2017
DOI: 10.1515/dx-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of electronic health records on diagnosis

Abstract: Diagnostic error may be the largest unaddressed patient safety concern in the United States, responsible for an estimated 40,000-80,000 deaths annually. With the electronic health record (EHR) now in near universal use, the goal of this narrative review is to synthesize evidence and opinion regarding the impact of the EHR and health care information technology (health IT) on the diagnostic process and its outcomes. We consider the many ways in which the EHR and health IT facilitate diagnosis and improve the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 81 publications
1
64
0
1
Order By: Relevance
“…Echoing Nguyen et al’s evaluation [ 68 ], there was also a perception that patient safety and care quality could benefit from EMR introduction, by supporting the audit-and-feedback process, alongside improved medication management. However other reviews have found less conclusive evidence for this point [ 66 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Echoing Nguyen et al’s evaluation [ 68 ], there was also a perception that patient safety and care quality could benefit from EMR introduction, by supporting the audit-and-feedback process, alongside improved medication management. However other reviews have found less conclusive evidence for this point [ 66 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 While some literature suggests that EHRs have improved both quality and safety of health care, 20,21 significant safety risks in patient care continue to be associated with the use of EHRs. 22,23 These risks include morbidity and mortality, 24 diagnostic errors, 25 disruptions in clinical workflow, and negative effects on patient-provider interactions. 26 These safety issues have led to a call to be more proactive in preventing errors through better EHR design.…”
Section: Background and Significancementioning
confidence: 99%
“…Today, diagnosticians must filter, integrate, and interpret information from diverse sources. Some studies suggest the EHR may facilitate this process through better information sharing and timely access to data [5,6,7,8]. However, studies also raise concerns ranging from fragmentation of data, information siloes, and data overload [9,10,11,5].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest the EHR may facilitate this process through better information sharing and timely access to data [5,6,7,8]. However, studies also raise concerns ranging from fragmentation of data, information siloes, and data overload [9,10,11,5]. For example, some studies have shown that EHRs influence physician workflow, workload, and communication practices [12]; while others suggest that more computer time, means less patient time [13] leading physicians to be perceived as less effective communicators [14].…”
Section: Introductionmentioning
confidence: 99%